Efektiftas Program Bantuan Modal Berupa Barang terhadap Usaha Mikro di Kelurahan Nipah Panjang II - Winarni, Etik; Sari, Yolanda; Zulfa, Indana (Universitas Batanghari Jambi, 2025)
The purpose of this study is to determine the strategies that can be used to advance and create a more effective capital assistance program in helping economic growth. This research design uses a quantitative descriptive method. The results of the SWOT analysis of the strengths of the capital assistance program in the form of goods for micro businesses. In addition, there is an opportunity to develop programs online or digitally to reach more beneficiaries and accelerate the process of business development, increase production value and income and business profits so that businesses grow. While the main weaknesses in the business capital assistance program are the lack of introduction, promotion, information and lack of skill levels or knowledge of using capital assistance. as well as the threat of capital assistance programs in the form of rapidly developing technological risks that can make the capital assistance program provided obsolete or out of date, increasingly tight business competition in the market, thereby reducing the sustainability of business recipients of capital changes from government policies that can reduce capital assistance programs.